Dentoskeletal and soft tissue changes after treatment of crowding with premolar extractions: a 50-year follow-up. (6th July 2022) - Al-Taai, Nameer; Persson, Maurits; Ransjö, Maria; Levring Jäghagen, Eva; Westerlund, Anna
Summary: Background: The long-term effects on dentofacial morphology of interceptive treatment with premolar extractions, in the absence of subsequent orthodontic treatment, have not been fully explored. Objective: The aim was to investigate the effects of premolar extractions (without subsequent orthodontic treatment) on the dentoskeletal and soft tissue profile of patients aged between 12 and 62 years with Class I malocclusion with severe crowding, as compared to untreated controls. Materials and methods: The Extraction group ( N = 30 with Class I crowding malocclusion) had their first premolars removed in early adolescence without subsequent orthodontic treatment. The Control group included 30 untreated subjects with Class I normal occlusion. Cephalograms were taken at 12 (T1), 15 (T2), 30 (T3), and 62 (T4) years of age. A superimposition-based cephalometric method was used to assess the dentoskeletal and soft tissue changes. Results: There were no significant differences between the Extraction and Control groups in terms of skeletal sagittal relation, incisor inclination, and protrusion, or most of the soft tissue parameters throughout the observation period. However, significant differences were observed between the groups with respect to the vertical relations in T2–T3, such that the Extraction group showed more-pronounced decreases in the ML/NSL, ML/NL, and Gonial angles and more-pronounced increases in facial heights. Conclusions and implications: Treatment for subjects with Class I malocclusion with severe crowding by the extraction of four premolars, without subsequent orthodontic treatment, does not affect the long-term dentoskeletal and soft tissue profile, as compared to an untreated Control group. The degree of crowding, rather than changes in dentofacial morphology, is crucial in deciding on extraction therapy.